Oral Anticoagulation Therapy in Pediatric Patients: a Prospective Study - Andrew, Maureen; Marzinotto, Velma; Brooker, Lu Ann; Adams, Margaret; Ginsberg, Jeff; Freedom, Robert; Williams, William (Thrombosis and Haemostasis, 1994)
There are no validated guidelines for administering or monitoring oral anticoagulant therapy in pediatric patients. A pediatric thromboembolism program at the Hospital for Sick Children, Toronto, prospectively monitored consecutive children requiring warfarin over an 18 month period. A uniform protocol was followed and dose adjustments based upon international normalized ratios (INRs). One hundred and fifteen consecutive children; 68 males and 47 females, received warfarin. The age distribution was: <ly (19); 1-5 ys (33); 6-10ys (20); 11-18 ys (43). Warfarin was used for secondary prevention of venous thromboembolism (n = 56) and primary prevention of thromboembolism (n = 59). Underlying disorders included: congenital heart disease (CHD) without mechanical valves (MV) (49); CHD with MV (18); cancer (8); longterm total parenteral nutrition (7); renal disorders (10); other (23). Treatment length was considered as short term (3-6 mths) n = 37 (32%); longterm (> 6 mths) n = 38 (33%); and lifelong n = 40 (35%) of children. While receiving warfarin, 95 children received concurrent longterm treatment with other drugs: 1 drug (28); 2 drugs (27); 3 drugs (21); 4 or more drugs (19).The amounts of warfarin/kg required to achieve INRs of 2 to 3 decreased with increasing age. Children <1 year of age required 0.32 ± 0.05 mg/kg whereas children 11-18 yrs required 0.09 ± 0.01 mg/kg; P <0.001. Monitoring warfarin required an average of 4.0 measurements per month and 1.5 dose changes per month. Changes in warfarin doses were primarily precipitated by drugs, intermittent illness, and changes in diet. A subgroup of children (n = 21) were treated with low dose warfarin either alone (n = 14) or following a course of full dose therapy (n = 7) to achieve an INR of 1.3 to 1.8. These children had persisting predisposing causes for new or recurrent thromboembolism. After the age of 1, the average dose required was 0.08 ± 0.01 mg/kg.Complications were rare. Two children had significant bleeding events that resolved without further morbidity. There were no recurrent thrombotic events while children were receiving warfarin. In summary, warfarin therapy is age and weight dependent in children; close monitoring is necessary because of changing requirements; and complications are infrequent when management is coordinated through one service.